Multi frequency matching for voltage waveform tailoring. (25th September 2018) - Schmidt, Frederik; Schulze, Julian; Johnson, Erik; Booth, Jean-Paul; Keil, Douglas; French, David M; Trieschmann, Jan; Mussenbrock, Thomas
Abstract: Customized voltage waveforms composed of a number of frequencies and used as the excitation of radio-frequency plasmas can control various plasma parameters such as energy distribution functions, homogeneity of the ion flux, or ionization dynamics. So far this technology, while being extensively studied in academia, has yet to be established in applications. One reason for this is the lack of a suitable multi frequency matching network that allows for maximum power absorption for each excitation frequency that is generated and transmitted via a single broadband amplifier. In this work, a method is introduced for designing such a network based on network theory and synthesis. Using this method, a circuit simulation is established that connects an exemplary matching network to an equivalent circuit plasma model of a capacitive radio-frequency discharge. It is found that for a range of gas pressures and number of excitation frequencies the matching conditions can be satisfied, which proves the functionality and feasibility of the proposed concept. Based on the proposed multi frequency impedance matching, tailored voltage waveforms can be used at an industrial level.